Disease Pattern at Medicine Outpatient Department of A Tertiary Care Hospital - Akter, Raushan; Uddin, M Jalal; Biswas, Rajat Sankar Roy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : Bangladesh, like many transitional nations, is straddling with the demographic and epidemiological transition. There is a critical need to improve public health in this region. But number of studies & representative data on the prevalence of diseases is inadequate. The objective of this study is to detect type & frequency of diseases among patients attending in medicine outpatient department (OPD) to improve the quality of healthcare. Materials and methods: This observational study was conducted at the outpatient department (OPD) of Chattogram Maa-O-Shishu Hospital Medical College from February to April 2018. Purposive sampling was used. Total 500 patients were included. Details were recorded in a data form and diagnosis was made on the basis of history, physical examination and necessary laboratory investigations. Data were collected and analyzed using the SPSS Version 20. Results : Total 500 patients were evaluated. Majority were female (61.2%). Highest number of patients i.e. 299 (59.4%) belonged to the age group of 16–35 years. Majority 405 (81%) of the patients in our study were from surrounding locality (Urban). The most common diseases was DM affecting 55(11%). HTN was 2nd common disease 51(10.2%). During this study we found gastrointestinal system was the most common affected organ system. Conclusion: Disease pattern study is very important to focus top problems, so that we can prepare ourselves to fight against them. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 27-30